Rising storm - Hunter, Erin (Hunter, Erin. Warriors, 2004)
Fireheart, the warrior cat, faces many challenges in his new role of ThunderClan deputy as his apprentice, Cloudpaw, resists following the warrior code, Bluestar weakens, and Tigerclaw continues to haunt the forest seeking revenge.